Collider Bias Is Only a Partial Explanation for the Obesity Paradox. Issue 4 (July 2016) - Sperrin, Matthew; Candlish, Jane; Badrick, Ellena; Renehan, Andrew; Buchan, Iain
Abstract : Background: "Obesity paradox" refers to an association between obesity and reduced mortality (contrary to an expected increased mortality). A common explanation is collider stratification bias: unmeasured confounding induced by selection bias. Here, we test this supposition through a realistic generative model. Methods: We quantify the collider stratification bias in a selected population using counterfactual causal analysis. We illustrate the bias for a range of scenarios, describing associations between exposure (obesity), outcome (mortality), mediator (in this example, diabetes) and an unmeasured confounder. Results: Collider stratification leads to biased estimation of the causal effect of exposure on outcome. However, the bias is small relative to the causal relationships between the variables. Conclusions: Collider bias can be a partial explanation of the obesity paradox, but unlikely to be the main explanation for a reverse direction of an association to a true causal relationship. Alternative explanations of the obesity paradox should be explored. See Video Abstract athttp://links.lww.com/EDE/B51 . Abstract : Supplemental Digital Content is available in the text.